The Developed Materials and Techniques and Its Role in Exposing the Aesthetic Of Art Work (Al-Academy, 2023)
This study is targeting the new developed materials and techniques and how they were affected by the scientific and technological developments that contributed to revelated new and varied developed materials and techniques. And from the artist’s formulation by using the materials and techniques and through its embodiment and sensor the values, artistic and aesthetic standards by breaking from the familiar in aesthetic contemporary way.The studies on questioning what’s the role of The New Developed Materials and Techniques in exposing the aesthetic of the art work?This study is to show the aesthetic of the art work through the new developed materials and techniques. Which was based on descriptive analyzing method and highlighted as the result on the study on the importance of the new developed materials and techniques which is considered unusual to build and artwork and contains a different art values and to keep up with the new industrial innovations by using it in forming the art work which enriches the field of art. Moreover, developing contemporary art works based on the aesthetics of developed materials and techniques and by using the un traditional methods it made it possible to have a different creative texture of forming, which contributes to expose a unique aesthetics value together by using new developed material in one art work.The study recommended the importance of following up the technology development of the materials and different possibilities of forming and the benefits in the art works. Furthermore, to raise aesthetic awareness by continuing on trying new materials and to figure out a new different forming connection in the art work.